Addition of short course radiotherapy in newly diagnosed locally advanced rectal cancers with distant metastasis. Issue 2 (7th February 2020) - Jain, Shanu; Engineer, Reena; Ostwal, Vikas; Ramaswamy, Anant; Chopra, Supriya; Desouza, Ashwin; Lewis, Shirley; Arya, Supreeta; Patil, Prachi; Saklani, Avanish
Abstract: Aim: To study the outcomes of patients presenting with locally advanced rectal cancers with distant metastasis (mLARC), treated with short course radiotherapy (SCRT). Method: Between May 2012 and August 2015, 70 patients diagnosed with mLARC, treated with SCRT (25 Gy/5#) and three to six cycles of CAPOX chemotherapy (CT), were assessed for surgical feasibility for the primary and metastatic sites. Results: Sixty‐five patients could complete the planned SCRT and three to six cycles of CT. Response rate and disease control rate for the primary was 68% and 97%, respectively. Radiologically, CRM became free in 44 (72%) patients out of 61 initially involved. Fifty‐two (74%) were planned to receive treatment with a potentially curative intent and 18 (26%) with palliative intent. Of those treated with curative intent, 34 (65%) underwent primary tumor resection (PTR). Successful intervention for metastatic disease was done in 27 (52%) patients. At a median follow up of 43 months, the median overall survival (OS) for patients undergoing PTR was 36 months versus 12 months for those in which the tumor was still unresectable or had distant progression ( P  < .001). Of the operated patients, 56% were alive at the end of 3 years. The median pelvic recurrence free survival was 29 months. Symptom control in the form of pain and bleeding control was observed in 80%. Conclusion: The addition of SCRT to CT in mLARC can downstage the primary tumor to undergo surgery, thereby, achieving better loco‐regional control and survival. It achieves good palliation in patients unable to undergo surgery due to extensive primary or metastatic disease.